PENGARUH PENDAPATAN ASLI DAERAH, DANA PERIMBANGAN, DAN SISA LEBIH PERHITUNGAN ANGGARAN TERHADAP BELANJA DAERAH SERTA ANALISIS FLYPAPER EFFECT (Studi pada Pemerintah Daerah Kabupaten/Kota di Provinsi Jawa Timur) - SE, Fibriana (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The objectives of this research are to examine the effect of own-source revenue (PAD), counter balance funds, such as revenue sharing (DBH), general purpose grant (DAU), and specific purpose grant (DAK), and remaining budget surplus (SiLPA) on local ependitures and to analyze the potential of flypaper effect in local expenditure. The population of this study is all regencies and cities in East Java. The data of this study are audited Budget Realization Statements from 2015 to 2016 obtained from Indonesian Audit Board. The results of multiple linier analysis show that PAD, DAU, and DAK have significant influence, while DBH and SiLPA do not have significant influence on Local Expenditure. In addition, flypaper effect does not occur in Local Expenditure.Keywords: own-source revenue, revenue sharing, general purpose grant, specific purpose grant, remaining budget surplus, flypaper ffect, local expenditure